Eye tracking to support assessment of patients with prolonged disorder of consciousness – a case series - Jan Johansson; Marika Möller; Kristina Franzon; Jonas Stenberg; Alison K. Godbolt (Journal of Rehabilitation Medicine)
Objective: To investigate if eye tracking can support detection of covert voluntary eye movements and to compare these findings with a simultaneously performed clinical assessment according to the Coma Recovery Scale manual regarding visual stimuli.